Make up your mind about food: A healthy mindset attenuates attention for high-calorie food in restrained eaters. (1st October 2016) - Werthmann, Jessica; Jansen, Anita; Roefs, Anne
Abstract: Attention bias for food could be a cognitive pathway to overeating in obesity and restrained eating. Yet, empirical evidence for individual differences (e.g., in restrained eating and body mass index) in attention bias for food is mixed. We tested experimentally if temporarily induced health versus palatability mindsets influenced attention bias for food, and whether restrained eating moderated this relation. After manipulating mindset (health vs. palatability) experimentally, food-related attention bias was measured by eye-movements (EM) and response latencies (RL) during a visual probe task depicting high-calorie food and non-food. Restrained eating was assessed afterwards. A significant interaction of mindset and restrained eating on RL bias emerged, β  = 0.36, t (58) = 2.05, p  = 0.045: A health mindset – as compared to a palatability mindset – attenuated attention bias for high-caloric food only in participants with higher eating restraint. No effects were observed on EM biases. The current results demonstrate that state differences in health versus palatability mindsets can cause attenuated attention bias for high-calorie food cues in participants with higher eating restraint. Our findings add to emerging evidence that state differences in mindsets can bias attention for food, above the influence of trait differences.